The System-Wide Effect of Real-Time Audiovisual Feedback and Postevent Debriefing for In-Hospital Cardiac Arrest: The Cardiopulmonary Resuscitation Quality Improvement Initiative*. Issue 11 (November 2015) - Couper, Keith; Kimani, Peter K.; Abella, Benjamin S.; Chilwan, Mehboob; Cooke, Matthew W.; Davies, Robin P.; Field, Richard A.; Gao, Fang; Quinton, Sarah; Stallard, Nigel; Woolley, Sarah; Perkins, Gavin D.
Abstract : Objective: To evaluate the effect of implementing real-time audiovisual feedback with and without postevent debriefing on survival and quality of cardiopulmonary resuscitation quality at in-hospital cardiac arrest. Design: A two-phase, multicentre prospective cohort study. Setting: Three UK hospitals, all part of one National Health Service Acute Trust. Patients: One thousand three hundred and ninety-five adult patients who sustained an in-hospital cardiac arrest at the study hospitals and were treated by hospital emergency teams between November 2009 and May 2013. Interventions: During phase 1, quality of cardiopulmonary resuscitation and patient outcomes were measured with no intervention implemented. During phase 2, staff at hospital 1 received real-time audiovisual feedback, whereas staff at hospital 2 received real-time audiovisual feedback supplemented by postevent debriefing. No intervention was implemented at hospital 3 during phase 2. Measurements and Main Results: The primary outcome was return of spontaneous circulation. Secondary endpoints included other patient-focused outcomes, such as survival to hospital discharge, and process-focused outcomes, such as chest compression depth. Random-effect logistic and linear regression models, adjusted for baseline patient characteristics, were used to analyze the effect of the interventions on study outcomes. In comparison with no intervention, neither real-time audiovisual feedback (adjusted odds ratio, 0.62; 95% CI, 0.31–1.22; p = 0.17) nor real-time audiovisual feedback supplemented by postevent debriefing (adjusted odds ratio, 0.65; 95% CI, 0.35–1.21; p = 0.17) was associated with a statistically significant improvement in return of spontaneous circulation or any process-focused outcome. Despite this, there was evidence of a system-wide improvement in phase 2, leading to improvements in return of spontaneous circulation (adjusted odds ratio, 1.87; 95% CI, 1.06–3.30; p = 0.03) and process-focused outcomes. Conclusions: Implementation of real-time audiovisual feedback with or without postevent debriefing did not lead to a measured improvement in patient or process-focused outcomes at individual hospital sites. However, there was an unexplained system-wide improvement in return of spontaneous circulation and process-focused outcomes during the second phase of the study. Abstract : Supplemental Digital Content is available in the text.